PKM PENGELOLAAN AIR BERSIH TIRTA AGUNG DESA WRINGIN KURUNG BARU KABUPATEN GRESIK - Nugroho, Alfi; Sujani, Sujani; Ritonga, Alven Safik (Jurnal Abdimas Sang Buana, 2024)
Wringin Kurung Hamlet is one of the hamlets of Gresik Regency, in 2016 a 100m deep well was drilled in this area as well as the construction of a 12 cubic tank with assistance from the government. Currently, HIPPAM managing Tirta Agung's clean water has been distributed to 271 residents' homes. HIPPAM management is still very simple, the HIPPAM organizational structure only consists of a Chairman, deputy elders, Secretary, Treasurer, technicians and operations. The method refers to the objectives of the activities that have been determined, namely the problem of producing water from the well directly pumped into reservoirs and then distributed to residents, so that the water is often accompanied by sand and is sometimes cloudy. There is no spare pump and pipe for the prospective new well because the source is located far from the source and installing new pumps, repairing and assisting tertiary pipe installations and adding plug n play filters in several tertiary channels. Internalizing a good work culture in the management environment by holding training and mentoring on organizational culture, structuring human resources, providing a sipemeter application used for recording water meters, knowing income, expenses and profit and loss from partners, apart from this, training and mentoring for new businesses has been carried out wash the motorbike. In this new business, the team provides assistance and training to partners, both in terms of management and financial management.